Taxonomic reassessment of Impatiens verecunda (Balsaminaceae) and its synonymization with I. cordata in the Western Ghats, India - Anitha, M.A.; Thomas, Sinjumol; Mani, Bince (Rheedea, 2026)
Historical records, such as those by J.D. Hooker and subsequent studies, have noted taxonomic complexities in Impatiens verecunda Hook.f. and its relationship with I. cordata Wight and I. anaimudica C.E.C.Fisch. Field surveys in Devikulam, Kerala, discovered specimens resembling I. verecunda, prompting detailed morphological comparisons with I. cordata and I. anaimudica. The plants exhibited similarities to I. cordata, differing only in habitat-driven traits like short stature and short floral spurs, confirmed the synonymization of I. verecunda under I. cordata. Conversely, I. anaimudica remains distinct due to its lenticelled stems, crimson flowers, and unique spur morphology. Further studies on I. cordata populations revealed variations in life history, habit, flower color, spur length, and floral morphology, influenced by environmental conditions. A revised description of I. cordata is presented to account for these variations and clarify its distinction from closely related taxa like I. elegans Bedd.